The rivalry of the great powers for Albanian hydrocarbons, 1920-1926 - Mentor Hasani; Gazmend S. Rizaj (The Journal of European Economic History (JEEH), 2023)
The paper aims to analyze the economic interests of some of the Balkan countries and Great Powers in Albania's resources above and below ground with a focus on hydrocarbons. It covers the pe- riod 1920-1926, specifically after the end of World War I when some of the Balkan states and Great Powers sought to influence Albania's political system through their economic presence in the country. Because of Albania's undefined political status, there was even more impetus to establish claims, attracting the investment of hydrocarbon companies in Albania. Aware of its unfavourable eco- nomic position, the Albanian government sought support from pow- erful Western states and business corporations etc. as the only viable means and opportunity to overcome the legacy of economic stagnation inherited from Ottoman rule. The Great Powers and their respective industries engaged in intense rivalry in the period after the end of World War I, particularly in the period 1920-1926, be- cause of their interest in Albania's mineral resources. For the Alba- nian government administrations of the 1920s, the granting of concessions for the exploitation of Albania's resources entered a particularly difficult phase as, in making economic decisions, the po- litical interests of Albania regularly clashed with the governments of competing companies. The rivalry between British, Italian, American, and French oil companies for concessions to exploit Albania's mineral resources was accompanied by constant diplomatic pressure on the Albanian government and parliament. Research and discussion of this topic are based on analytical, statistical, and comparative methods. Both unpublished and published archival sources of Albanian and Western provenance have been used in conjunction with the relevant literature.
Keywords: 330; Raw material; History; Albania; Rohstoff; Geschichte; Albanien